TELAAH STRUKTURALISME GENETIK LUCIEN GOLDMANN DALAM PENGKAJIAN KARYA SASTRA PUISI GADIS PEMINTA-MINTA KARYA TOTO SUDARTO - Priharyani, Vivi; Sholah, Ibnu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This article attempts to discuss the study of genetic structuralism by Lucien Goldman in his study of the begging girl poem by Toto Sudarto. In the theory of genetic structuralism, Goldman builds a set of interrelated categories, namely human facts, reflective subject, structure, author's worldview, and explanation. The author uses a qualitative research approach, a study that tries to understand the problem holistically in a descriptive way. The steps used in analyzing the poems are: (a) collecting Toto Sudarto poems; (b) reading and understanding Toto Sudarto poetry; (c) analyzing genetic structuralism in Toto Sudarto poetry; (d) describing the results of the analysis. The research results of this article are in the form of poetry analysis which refers to the points; social activity, reflective subject analysis, and dialectical methods. Keywords: genetic structuralism, Lucien Goldman, poetry